Behind the design [ designers on designing - Arnold, Brian; Eddy, Brendan; Hagre, Neil (Thomson Delmar Learning, 2007)
Interviews with designers from three design firms, Nita B. Creative, Werner Design Werks, and Planet Propaganda, with samples of design work completed for particular projects and discussion of their various stages from conception through production. Nita B. Creative is represented by a project completed for Community Health Charities; Planet Propaganda by its design of the 2006 Gary Fisher Mountain Bikes catalog; and Werner Design Werks by its design of a brochure and brand identity for Inspiration Neighborhood, a residential development